Neighbourhood selection and neighbourhood matching: Choices, outcomes and social distance - Clark, W.A.V.; ViforJ, Rachel; Truong, Khuong (SAGE PUBLICATIONS LTD, 2022)
In this article, we ask how well Australian households are matched to their neighbourhood social environments. We broadly replicate a previous study of matching and ask to what extent households live in communities that are similar in socio-economic status to their characteristics. And, when households move, do they relocate in such a way as to increase similarity to their neighbours? The processes are at the heart of understanding the urban structure, how it changes over time and the links to urban inequality. The article uses data on household incomes from the Household, Income and Labour Dynamic (HILDA) Survey to measure the degree of similarity between households and their neighbours. We study the variation in matching for the population as a whole, and by quintiles of median neighbourhood income. We also measure how individuals that change neighbourhoods increase their similarity to the destination neighbourhood. We find that with respect to matching there is considerable diversity in the levels of matching; and that with respect to residential change, households in general do not make major shifts to increase matching when we control for housing tenure and other household characteristics. There is a need for further replications to understand the nature of matching and the outcomes.